Mechanism underlying the involvement of CXCR4/CXCL12 in diabetic wound healing and prospects for responsive hydrogel-loaded CXCR4 formulations - Wang, Lingli; Nie, Fengsong; Lu, Zhaoyu; Chong, Yang (Frontiers in Pharmacology, 2025)
Diabetes mellitus is a prevalent chronic disease, often leading to complications, with chronic wounds being among the most challenging. Impairment of the CXCR4/CXCL12 signaling pathway, which plays a key role in cell mobilization, migration, and angiogenesis, significantly hampers the wound healing process in diabetic patients. Modulation of this pathway using CXCR4-targeted agents has shown promise in restoring wound repair capabilities. Additionally, the development of responsive hydrogels capable of adapting to external stimuli offers a powerful platform for drug delivery in chronic wound management. These hydrogels, when loaded with CXCR4 agonists or antagonists, enable controlled drug release and real-time therapeutic modulation. Integrating such hydrogels with existing wound healing strategies may provide an innovative and effective solution for overcoming the challenges associated with diabetic wound treatment.